2022
DOI: 10.1063/5.0077408
|View full text |Cite
|
Sign up to set email alerts
|

Impact of confinement and polarizability on dynamics of ionic liquids

Abstract: Polarizability is a key factor when it comes to an accurate description of different ionic systems. The general importance of including polarizability into molecular dynamics simulations was shown in various recent studies for a wide range of materials, ranging from proteins to water to complex ionic liquids and for solid-liquid interfaces. While most previous studies focused on bulk properties or static structure factors, this study investigates in more detail the importance of polarizable surfaces on the dyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…In a very recent work, Gäding et al have investigated the effect of pore wall polarizability on ion diffusion for 1-butylpyridinium bis­(trifluoromethane) sulfon-imide [BuPy]­[NTf 2 ] ionic liquid. They found that for polarizable pore walls, the diffusion coefficient was about 20% lower for a 4.1 nm slit but more than 80% higher for a 1.65 nm slit compared to nonpolarizable (constant charge) pore walls.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very recent work, Gäding et al have investigated the effect of pore wall polarizability on ion diffusion for 1-butylpyridinium bis­(trifluoromethane) sulfon-imide [BuPy]­[NTf 2 ] ionic liquid. They found that for polarizable pore walls, the diffusion coefficient was about 20% lower for a 4.1 nm slit but more than 80% higher for a 1.65 nm slit compared to nonpolarizable (constant charge) pore walls.…”
Section: Simulationsmentioning
confidence: 99%
“…For smooth walls (no atomistic structure), they found noticeable differences only for negative potentials, while for graphite-like walls, the differences were noticeable, albeit small, in the whole voltage range. In a very recent work, Gading et al 303 have investigated the effect of pore wall polarizability on ion diffusion for 1butylpyridinium bis(trifluoromethane) sulfon-imide [BuPy]-[NTf 2 ] ionic liquid. They found that for polarizable pore walls, the diffusion coefficient was about 20% lower for a 4.1 nm slit but more than 80% higher for a 1.65 nm slit compared to nonpolarizable (constant charge) pore walls.…”
mentioning
confidence: 99%
“…Several factors including pore size distribution, pore conductivity, pore connectivity, charging dynamics, and ion concentration will affect ionic diffusion or the flow of ions in and out of the pores. [ 57 , 58 , 59 , 60 , 61 , 62 ] Among them, pore size is the most important factor. In this section, ion transport in nanoscale (2–100 nm) and microporous (typical below 2 nm) will be introduced separately due to their different interaction forces.…”
Section: Artificial Nanoionicsmentioning
confidence: 99%
“…33,43,50,51,55,56,[76][77][78] However, previous studies showed that the polarizability of charged systems influences not only the phase transition but also the transport properties such as ionic conductivities. [79][80][81][82][83][84][85][86][87][88][89] For example, Borodin et al showed that the diffusion constants of ionic liquids were significantly enhanced by a factor of about two with polarizable force fields. 38,79,90 In this section, we present our recent results about the effect of ion polarization to the rotational dynamics of OIPCs.…”
Section: Effect Of Polarization On the Rotational Diffusion In Oipcsmentioning
confidence: 99%